Pengukuran Risiko dan Expected Value pada Keputusan Pemasaran Bancassurance di Industri Keuangan - Akbar, Rahmat; Zain, Irsyadi; Nefrida (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
This study aims to analyze the influence of perceived risk, product benefits, and marketing communication quality on customers’ decisions to purchase bancassurance products using the expected value approach. This approach is employed to explain how customers evaluate the probabilities of potential benefits and risks before making decisions under conditions of uncertainty. Primary data were collected through a questionnaire that was validated using expert-based content validity and tested for reliability using Cronbach’s Alpha. Data were analyzed using descriptive techniques and decision analysis based on expected value. The results indicate that perceived risk, product benefits, and marketing communication quality significantly affect purchasing decisions, with communication quality emerging as the most dominant factor. A higher expected value significantly increases customers’ likelihood of choosing bancassurance products. These findings highlight the importance of transparent information, enhanced product benefits, and simplified risk structures in improving bancassurance marketing effectiveness. This study contributes to the development of risk-based marketing strategies in the financial industry and offers empirical insights for banks in designing more competitive marketing communications and protection products.